Atmospheric deposition of chlorinated and brominated polycyclic aromatic hydrocarbons in central Europe analyzed by GC-MS/MS - Jin, Rong; Bandowe, Benjamin A Musa; Zheng, Minghui; Liu, Guorui; Nežiková, Barbora; Prokeš, Roman; Čupr, Pavel; Klánová, Jana; Lammel, Gerhard (Environmental science and pollution research international, 2021)
Chlorinated and brominated polycyclic aromatic hydrocarbons (ClPAHs and BrPAHs) are persistent organic pollutants that are ubiquitous in the atmospheric environment. The sources, fate, and sinks in the atmosphere of these substances are largely unknown. One of the reasons is the lack of widely accessible analytical instrumentation. In this study, a new analytical method for ClPAHs and BrPAHs using gas-chromatography coupled with triple quadrupole mass spectrometry is presented. The method was applied to determine ClPAHs and BrPAHs in total deposition samples collected at two sites in central Europe. Deposition fluxes of ClPAHs and BrPAHs ranged 580 (272-962) and 494 (161-936) pg m-2 day-1, respectively, at a regional background site, Košetice, and 547 (351-724) and 449 (202-758) pg m-2 day-1, respectively, at a semi-urban site, Praha-Libuš. These fluxes are similar to those of PCBs and more than 2 orders of magnitude lower than those of the parent PAHs in the region. Seasonal variations of the deposition fluxes of these halogenated PAHs were found with maxima in summer and autumn, and minima in winter at Košetice, but vice versa at Praha-Libuš. The distribution of ClPAHs and BrPAHs between the particulate and dissolved phases in deposition samples suggests higher degradability of particulate BrFlt/Pyr and BrBaA than of the corresponding ClPAHs. A number of congeners were detected for the first time in the atmospheric environment.
Keywords: polycyklické aromatické uhlovodíky; tandemová hmotnostní spektrometrie; látky znečišťující vzduch; Total deposition; Evropa; Gas Chromatography-Mass Spectrometry; Hydrocarbons, Chlorinated; Tandem Mass Spectrometry; Air Pollutants; Analytical method; plynová chromatografie s hmotnostně spektrometrickou detekcí; Polycyclic Aromatic Hydrocarbons; monitorování životního prostředí; Environmental Monitoring; Triple quadrupole mass spectrometry; Wet and dry deposition; chlorované uhlovodíky; Europe; polychlorované bifenyly; Polychlorinated Biphenyls; Halogenated PAHs